Tobin's Q and Market Bubble Phenomenon in Indonesia Property Sector in 2011-2013 - Farrosi, Faishal Ahmad; Nugroho, Anggoro Budi (Journal of Business and Management, 2014)
Property has been one of the most interesting subject for investment since people believe that the prices of property won’t fall, but that kind of expectation can lead to irrational exuberance which can trigger bubble condition. Many media issued that Indonesia has shown the sign of bubble in property sectors, but is there really a bubble in the property or is it because the demand that is higher than the supply. The method that is chosen to analyze this research is valuing the 4 most liquid stocks in property sector using discounted cashflow valuation and then compares it with the market value. The result then analyzed using paired sample t-test to see whether there is significant difference between the market value and book value. The result shows that there is no significant difference between the market value and book value of property sectors which mean there hasn’t been any bubble sign in the property market. The increase or property prices aren’t caused by the speculation of the investors but it is supported by a massive amount of demands that excess the supply of housing in Indonesia. Even though there is no bubble sign in the property sector, there is a company that has a significant difference between market value and book value with the market value is bigger than the book value. It means that the company has shown a bubble sign which can be dangerous for investor if someday the bubble burst and make the stock price fall. Indonesia as a developing country shows that its fundamental economy condition is still good with no sign of bubble in the property sectors which is safe for investors and home buyers to buy property since the prospect for the future is good since the demand is double than the supply. Keywords Property, valuation, paired t-test, investment, stocks, bubble